THE EFFECT OF WORK LIFE BALANCE AND WORK FLEXIBILITY ON THE PERFORMANCE OF MILLENNIAL EMPLOYEES - Hendri Indra (Jurnal Penelitian Samudra, 2026)
Akademi Maritim Belawan hendriindra806@gmail.com ABSTRACT This study aims to examine the effect of work-life balance and work flexibility on the performance of millennial employees. Millennials represent a dominant segment of the workforce and demonstrate unique characteristics, including a strong preference for flexibility and balance between personal and professional life. This research employs a quantitative approach using a survey method. Data were collected from 120 millennial employees working in private and public organizations. Multiple linear regression analysis was used to test the hypotheses. The results show that work-life balance has a positive and significant effect on employee performance, while work flexibility also has a positive and significant influence on performance. Simultaneously, work-life balance and work flexibility significantly affect the performance of millennial employees. These findings highlight the importance of adaptive human resource management practices in improving organizational performance through enhanced employee well-being.